2019
DOI: 10.1055/a-0978-4972
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Placenta-Derived Mesenchymal Stem Cell Treatment for Diabetic Patients with Critical Limb Ischemia: A Pilot Study

Abstract: Aim Diabetic foot has become the main cause of non-traumatic amputation. Stem cell therapy, especially mesenchymal stem cells (MSCs), holds a great promise as a therapy for diabetic foot with ischemia limb arterial disease. The aim of this pilot study is to evaluate the safety and efficacy of placenta-derived MSCs (P-MSCs) treatment for diabetic patients with critical limb ischemia (CLI). Methods Four eligible diabetic patients with CLI were consecutively enrolled in this pilot study. On the base of the stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Numerous clinical trials have demonstrated that cell-based therapies can help individuals with CLI. Only three phase I clinical studies that examined the tolerability and viability of P-MSCs for CLI have published the nal results from these trials (20,(39)(40)(41). However, no clinical research has documented the safety and effectiveness of utilizing P-MSCs to treat patients suffering from non-atherosclerotic PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical trials have demonstrated that cell-based therapies can help individuals with CLI. Only three phase I clinical studies that examined the tolerability and viability of P-MSCs for CLI have published the nal results from these trials (20,(39)(40)(41). However, no clinical research has documented the safety and effectiveness of utilizing P-MSCs to treat patients suffering from non-atherosclerotic PAD.…”
Section: Discussionmentioning
confidence: 99%
“…New collateral vessels were detected by CTA 1 month after hUC-MSC injection intramuscularly in a case series study [ 54 ], which indicated that angiostenosis was alleviated. Similarly, the symptoms of limb ischaemia were relieved after intramuscular injection of MSC, although no significant improvements in ABPI or revascularization were detected [ 59 ]. However, few improvements were observed in the ankle-brachial pressure index (ABPI) and ankle pressure after intramuscular injection of MSCs in a controlled study [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…(22)(23)(24)(25)(26)(27)(28) Various clinical studies have demonstrated the safety and e cacy of umbilical cord and placental MSCs individually. (29)(30)(31)(32)(33)(34) For this study, a mixture of umbilical cord and placenta derived MSCs was used since, a mixture results in an enhanced outcome combining the bene ts of both types of cells. Invitro studies have shown that this mixture of cells secretes increased concentration of paracrine molecules such as IGF-1, KGF, VEGF, SDF-1α as compared to individual cell types which are responsible for stimulating lung repair, angiogenesis, stem cell recruitment, etc.…”
Section: Discussionmentioning
confidence: 99%